(untitled) (Canadian Medical Education Journal, 2023)
Background: Students are selected for admission to the Northern Ontario School of Medicine University (NOSM U) MD degree program using criteria aiming to maximize access of persons thought most likely to practice in the region, including use of a geographic context score (GCS) which ranks those with lived experience in northern Ontario and/or rurality most highly. This study investigates the effect of this admissions process upon medical school academic performance. Methods: We used a retrospective cohort design combined with multiple linear regression analysis to investigate the relationship between admission scores and performance on pre-clerkship courses, and the Medical Council of Canada Qualifying Exam Part 1 (MCCQE1). The GCS did not significantly explain performance variance on any pre-clerkship course, nor on the MCCQE1, while the undergraduate Grade Point Average correlated with most assessment scores. The number of prior undergraduate biomedical courses predicted science and clinical skills performance, particularly in Year 1, but not with MCCQE1 scores. Performance on Year 2 courses, particularly foundational sciences and clinical skills, significantly predicted MCCQE1 scores. Results: Our data suggest that admission geographic context scoring is unrelated to future academic performance. Further, students with fewer prior undergraduate biomedical courses may benefit from increased support and/or a modified program during the early years.